Social captial, legal institutions, and property rights: Overview - Quisumbing, Agnes R. (International Food Policy Research Institute, 2003)
The previous sections have highlighted the importance of assets as a determinant of bargaining power within marriage. Both formal and informal institutions underlie asset accumulation and provide the basis for property rights. When women face social and legal restrictions in acquiring certain forms of assets, such as land, they may resort to accumulating other “assets” and investing in other forms of capital. One of these forms of capital is social capital, which includes any networks that increase trust, ability to work together, access to opportunities, and reciprocity; informal safety nets; and membership in organizations (Chambers and Conway 1992; Scoones 1998; Devereux 2001; Adato and Meinzen-Dick 2002). For example, working through groups is one major mechanism through which outside programs and women themselves can improve their status (Quisumbing and Meinzen-Dick 2001; Dikito-Wachtmeister 2001). In fact, the networks and collective action that groups generate are now being recognized as an asset in itself. Social capital may be one asset in which women are less disadvantaged or even hold an advantage. Microfinance is perhaps the best-known type of program that works through women’s groups. Group savings, credit, and insurance programs for women substitute collective action through the groups for conventional assets (such as land) as collateral (Sharma 2001).